A brief history of surgical staplers in world and argentinian surgery - Da Lozzo, Alejandro (Revista del Hospital Italiano de Buenos Aires, 2013)
Surgical staplers are instruments used in surgery, which are intended to divide tissues in a quick and safe way. The Hungarians Victor Fischer and Hümer Hültl are the original inventors. This article describes the evolution of staplers throughout the history of Surgery and contributes with a brief history of the use of these devices in Argentina